2012
DOI: 10.1002/anie.201202704
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of α‐Oxygenated Ketones by the Dioxygenation of Alkenyl Boronic Acids

Abstract: Two in two: Dioxygenation of alkenyl boronic acids has been achieved with N-hydroxyphthalimide. The two-step process involves etherification of an alkenyl boronic acid with N-hydroxyphthalimide followed by a [3,3] rearrangement. The dioxygenated product can then be hydrolyzed to form either the corresponding α-hydroxy ketone or the α-benzoyloxy ketone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 62 publications
1
20
0
1
Order By: Relevance
“…[14] Microwave activation allowed decreasing the catalystl oading from 10 to 1.2 mol %, compared with thermal heating, and provided the olefin with perfect E selectivity.T he pinacol boronate product was then engaged in ab oroniodine exchange, to install (E)-iodoalkene 10 (E/Z ratio = 4:1), through as equence of boronate hydrolysis and halogenation in the presence of I 2 . [15] After extensive optimization of the reaction conditions, [16] the Suzuki-Miyaura reaction of 10 with freshly prepared boronic acid 11 [17] was successfully performed in the presence of PdCl 2 (dppf)·CH 2 Cl 2 [dppf = 1,1'-bis(diphenylphosphino)ferrocene],f ollowed by tert-butyldimethylsilyl (TBS) protection of the tertiary alcohol, giving 12 in 68 %y ield over two steps. Finally,e ster saponification and carboxyl activation as an imidazole amide [18] achieved the preparation of intermediate 13,prior to dienophile installation.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Microwave activation allowed decreasing the catalystl oading from 10 to 1.2 mol %, compared with thermal heating, and provided the olefin with perfect E selectivity.T he pinacol boronate product was then engaged in ab oroniodine exchange, to install (E)-iodoalkene 10 (E/Z ratio = 4:1), through as equence of boronate hydrolysis and halogenation in the presence of I 2 . [15] After extensive optimization of the reaction conditions, [16] the Suzuki-Miyaura reaction of 10 with freshly prepared boronic acid 11 [17] was successfully performed in the presence of PdCl 2 (dppf)·CH 2 Cl 2 [dppf = 1,1'-bis(diphenylphosphino)ferrocene],f ollowed by tert-butyldimethylsilyl (TBS) protection of the tertiary alcohol, giving 12 in 68 %y ield over two steps. Finally,e ster saponification and carboxyl activation as an imidazole amide [18] achieved the preparation of intermediate 13,prior to dienophile installation.…”
Section: Resultsmentioning
confidence: 99%
“…2. Several acyl groups were examined instead of the pivaloyl group, and the results revealed that the use of a smaller ester such as acetyl or isobutyryl group resulted in lower yields of 35 and 48%, respectively (Table 2, entries 13,14). To determine the effect of the electronic state of the ester of the outcome of the reaction, we also investigated several non-and monosubstituted benzoyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Based on the importance of α-acyloxyketones to chemistry, the development of a concise synthetic method for the preparation of α-acyloxyketone derivatives is important. Although a wide variety of synthetic methods have been investigated to date, 12,13) reports pertaining to the direct synthesis of α-acyloxyketone III by the oxidation of alkyne I are rare, most likely because of the difficulties associated with suppressing the over-oxidation of the product and controlling the regioselectivity of the reaction [14][15][16] (Chart 1). To allow for the direct synthesis of α-acyloxyketone III from alkyne I, several researchers directed their attention towards the transition metal-catalyzed migration of propargylic esters [17][18][19][20] to affect a facile oxidative transformation.…”
mentioning
confidence: 99%
“…Compound 7 was submitted to the modified Takai olefination in the presence of anhydrous CrCl 2 and CHI 3 at room temperature, to get the iodoalkene 8 in 77 % yield ( E / Z =11:1). A Suzuki–Miyaura cross‐coupling of 8 with ( Z )‐but‐2‐en‐2‐ylboronic acid 9 , in the presence of the commercially available catalyst PdCl 2 (dppf)⋅CH 2 Cl 2 (1.2 mol %), furnished diene 10 in 75 % yield with slight erosion of the E / Z ratio (8:1) despite optimization (dppf=1,1′‐bis(diphenylphosphino)ferrocene). After hydrolysis of the benzyl ester, the carboxylic acid was activated as an acylimidazole ( 11 ) to further install the lactam moiety…”
Section: Figurementioning
confidence: 99%